Anthropologists and Indians in the new South - Bonney, Rachel A.; Paredes, J. Anthony (James Anthony), 1939- (Contemporary American Indian studies., 2001)
An important collection of essays that looks at the changing relationships between anthropologists and Indians at the turn of the millennium. Southern Indians have experienced much change in the last half of the 20th century. In rapid succession since World War II, they have passed through the testing field of land claims litigation begun in the 1950s, played upon or retreated from the civil rights movement of the 1960s, seen the proliferation of "wannabe" Indian groups in the 1970s, and created innovative tribal enterprises-such as high-stakes bingo and gambling casinos-in the 1980s